Learning English from Tiktok : A Qualitative Case Study - Widagsa, Rudha; Fokatea, Muhammad Rizqun (Universitas PGRI Yogyakarta, 2024)
This study explores the use of TikTok as a medium for learning English, specifically targeting English as a Foreign Language learners (EFL). TikTok, as a widely popular social media platform, offers a unique opportunity for users to engage with diverse video content that can enhance their English skills, particularly in pronunciation, fluency, and comprehension. The primary objective of this research is to examine how EFL learners utilize TikTok to improve their English and to understand the impact of this platform on their learning process. The study employs a qualitative case study method, with data collected through in-depth interviews, participant observations, and analysis of TikTok content used by the participants. The findings reveal that TikTok is an effective tool for improving English skills among EFL learners. Participants reported significant improvements in pronunciation, fluency, and comprehension, along with increased motivation and interest in learning English due to TikTok's interactive and entertaining approach. This research contributes to the field of language education by highlighting the potential of digital media as an innovative and engaging learning tool. English educators are encouraged to incorporate TikTok into their teaching strategies to facilitate the development of English skills.